2022
DOI: 10.1093/ofid/ofac604
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-up of Human Immunodeficiency Virus-Associated Pulmonary Hypertension: Clinical Features and Survival Outcomes of the Pan Africa Pulmonary Hypertension Cohort (PAPUCO)

Abstract: Aims Data characterizing risk factors and long-term outcome studies on HIV-associated pulmonary hypertension (PH) in Africa are lacking. Methods The Pan African Pulmonary Hypertension Cohort, a multinational registry of 254 consecutive patients diagnosed with PH (97% of African descent) from nine centres in four African countries was implemented. We compared baseline characteristics and three-year survival of an HIV-infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A total of 95 full-text articles were assessed for eligibility. Articles assessed to have the incorrect denominator or no clear numerator were excluded as these missing elements would have precluded us from finding prevalence estimates [ 13 , 14 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 95 full-text articles were assessed for eligibility. Articles assessed to have the incorrect denominator or no clear numerator were excluded as these missing elements would have precluded us from finding prevalence estimates [ 13 , 14 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pooled cohort with active TB in this systematic review had a relatively young age, were less frequently smokers than the post-TB group and, although numbers are small, had a relatively high HIV prevalence (15% versus 11% in the global TB population) [ 1 ]. Data from the Pan African Pulmonary Hypertension Cohort (PAPUCO) showed that 5–7% of PH patients had active TB at the time of PH diagnosis, rising to 13% in the HIV population [ 13 , 14 ]. Although HIV may cause PH in its own right in approximately 0.5% of cases, the critical interplay between these two chronic infectious diseases and the combined effect on the pulmonary vasculature is unknown and is an important area of research [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this secondary analysis study of the Pan African Pulmonary Hypertension Cohort, a unique contemporary multi-country registry available to the continent [12][13][14][15] , we aimed to assess the effect of TB history on the prevalence and hazards of death associated with PH in the region with an important burden of HIV/TB coinfection, while also considering other emerging TB risk factors such as diabetes and chronic lung diseases on the rise on the continent. Our findings should rekindle debate about the proper management of noncommunicable diseases associated with TB care, as well as the need for effective universal health care to address the intersection of chronic communicable diseases and NCDs in Africa and other regions.…”
Section: Introductionmentioning
confidence: 99%